Reducing sound exposure during ocular vestibular evoked myogenic potential testing for superior semicircular canal dehiscence syndrome - Zuniga Manrique, Maria Geraldine; Schell, Angela; Engst, Benjamin G.; Carey, John P. (Otology & neurotology, 2021)
Background: Ocular vestibular evoked myogenic potentials (oVEMP) testing in response to air-conducted sound (ACS) has excellent sensitivity and specificity for superior semicircular canal dehiscence syndrome (SCDS). However, patients with SCDS may experience vertigo with the test, and recent works recommend minimizing acoustic energy during VEMP testing. Purpose: To develop an oVEMP protocol that reduces discomfort and increases safety without compromising reliability. Methods: Subjects: Fifteen patients diagnosed with SCDS based on clinical presentation, audiometry, standard VEMP testing, and computed tomography (CT) imaging. There were 17 SCDS-affected ears and 13 unaffected ears. In nine (53%) of the SCDS-affected ears surgical repair was indicated, and SCD was confirmed in each. oVEMPs were recorded in response to ACS using 500 Hz tone bursts or clicks. oVEMP amplitudes evoked by 100 stimuli (standard protocol) were compared with experimental protocols with only 40 or 20 stimuli. Results: In all three protocols, oVEMP amplitudes in SCDS-affected ears were significantly higher than in the unaffected ears (p < 0.001). 500 Hz tone bursts evoked oVEMPs with excellent (>90%) sensitivity and specificity in each of the three protocols. However, in the unaffected ears, lowering to 20 stimuli reduced the detection of oVEMP responses in some ears. Following surgical repair, oVEMPs normalized in each of the protocols. Conclusion: In oVEMP testing using ACS for SCDS, reducing the number of trials from 100 to 40 stimuli results in a more tolerable and theoretically safer test without compromising its effectiveness for the diagnosis of SCDS. Reducing to 20 stimuli may degrade specificity with clicks.